Nationalism and cosmopolitanism : a post-pandemic balance? - Teo, Terri-Anne (2020)
Reactions to COVID-19 suggest a resurgence of exclusionary nationalist sentiments, and the decline of social cohesion. The melding of national and global sensibilities may provide a remedy to an otherwise fractious future.